Comprehensive Methods of MALDI-TOF Mass Spectrometry Data Analysis - Plechawska-Wójcik, M. (Штучний інтелект, 2011)
The article presents a review of methods of MALDI-TOF data. There are many steps of mass spectrometry
data analysis. It is complex task and it should cover several platforms. It is important to do comprehensive
analysis to obtain useful results. The analysis should cover preprocessing and signals analysis, databases
searching and peaks classification. В статье представлен обзор методов MALDI-TOF данных с многошаговым спектрометрическим анализом.
Эта сложная задача должна охватывать несколько платформ. Чтобы получить полезные результаты, важно
сделать всеобъемлющий анализ. Подобный анализ должен охватывать анализ предварительной обработки
сигналов и анализ баз данных и поиска пиков классификации.